DIVERSIFICATION OF TOFU WASTE INTO TEMPE GEMBOS AND TEMPE RAGI IN TELUK SENTOSA VILLAGE - Zulkarnain Nasution; Henki Japina (PT. Jurnal Center Indonesia Publisher, 2025)
The diversification of tofu waste into soft tempeh and tempeh starter in Teluk Sentosa Village aims to optimize the utilization of tofu waste while increasing community income. Through participatory training, the community is taught techniques for processing tofu waste into value-added products. The results indicate that the produced soft tempeh has a tender texture and high nutritional value, while the tempeh starter shows good fermentation activity. Marketing these products has led to a significant income increase of approximately 30% within three months post-training. Additionally, this initiative contributes to waste reduction and enhances community awareness regarding sustainable resource management. It is hoped that this program can continue and provide positive impacts on the economy and environment in the village